2017
DOI: 10.1002/etc.3758
|View full text |Cite
|
Sign up to set email alerts
|

Combined environmental risk assessment for the antiviral pharmaceuticals ganciclovir and valganciclovir in Europe

Abstract: Potential environmental risks of the old antiviral pharmaceuticals ganciclovir (GCV) and valganciclovir (VGCV) were reassessed based on new environmental fate and chronic ecotoxicity tests and on actual use data for Europe. Valganciclovir is hydrolyzed to GCV by intestinal and hepatic esterases, and hence the new environmental tests only refer to GCV. A sorption study showed that GCV will not sorb significantly, excluding the soil as a relevant environmental compartment. Despite earlier data suggesting nondegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The physicochemical characteristics of AVDs (e.g., water solubility, chemical structure, and polarity) vary widely, and differences between the toxicities of different AVDs on organics have been observed. For example, the aquatic organism alga was inhibited by 4.86 mg/L nevirapine but not affected by 1000 mg/L ganciclovir (Ngumba et al 2016 ; Straub 2017 ). Nevertheless, the mechanisms underlying their toxicities’ differences remain unknown, which need to be further studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physicochemical characteristics of AVDs (e.g., water solubility, chemical structure, and polarity) vary widely, and differences between the toxicities of different AVDs on organics have been observed. For example, the aquatic organism alga was inhibited by 4.86 mg/L nevirapine but not affected by 1000 mg/L ganciclovir (Ngumba et al 2016 ; Straub 2017 ). Nevertheless, the mechanisms underlying their toxicities’ differences remain unknown, which need to be further studied.…”
Section: Resultsmentioning
confidence: 99%
“…The active metabolite of Tamiflu, oseltamivir carboxylate, was also reported to affect bacterial community structure mainly through stimulating α, β, and γ-Proteobacteria in aquatic ecosystems (Caracciolo et al 2010 ). However, the physicochemical characteristics of AVDs (e.g., water solubility, chemical structure, and polarity) vary widely, and differences between the ecotoxicities of different AVDs were observed (Azuma et al 2015 ; Ngumba et al 2016 ; Straub 2017 ). Almeida et al found that zidovudine was the least toxic to Ceriodaphnia dubia with half maximal effective concentration (EC 50 ) of 5.67 mg/L, while the species was sensitive to efavirenz with an EC 50 of 0.03 mg/L (Almeida et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A chronic ecotoxicity experiment performed using the antiviral pharmaceuticals ganciclovir (GCV) and valganciclovir (VGCV) with Raphidocelis subcapitata and Daphnia magna as test organisms did not reveal persistence or bioaccumulation (Straub 2017). In the same study, a comparison between predicted environmental concentrations (PECs) and predicted noeffect concentrations (PNECs) showed no significant risks for treated wastewater, surface water, groundwater or sediment; in addition, potential risks to (semi)aquatic top predators or to human consumers of water and fish were exceedingly low.…”
Section: Environmental Risk Assessment (Era)mentioning
confidence: 99%
“…[6][7][8] In order to overcome these limitations, it is a common strategy to convert one or more of the hydroxyl (OH) units in purine nucleosides to the corresponding ester groups to prepare purine nucleoside prodrugs for better performance. [9][10][11][12][13] Valganciclovir, the monoester derivative of ganciclovir, has better efficacy and bioavailability as an antiviral alternative. [14][15][16] Purines are mainly involved in metabolic processes, not only used as plant growth regulators, but also have good activity against plant viruses.…”
Section: Introductionmentioning
confidence: 99%